Rifle carriage affects gear distribution during on-snow skiing in female and male biathletes - Kårström, M. J.; Staunton, C.; McGawley, K.; Björklund, G.; Laaksonen, M. S. (Journal of Sports Sciences, 2022)
The aim was to investigate whether rifle carriage affects gear distribution during on-snow skiing in highly-trained biathletes, and whether there were any associated sex differences. Twenty-eight biathletes (11 women, 17 men) skied a 2230-m lap at competition speed twice, one lap with the rifle (WR) and the other lap without the rifle (NR). The biathletes wore a portable 3D-motion analysis system while skiing, which enabled characterisation of distance and time in different gears. Skiing WR increased lap time compared to NR (412 (90) vs. 395 (91) s, p < 0.001). The biathletes used gear 2 to a greater extent WR compared to NR (distance: 413 ± 139 vs. 365 ± 142 m; time: 133 (95) vs. 113 (86) s; both p < 0.001) and gear 3 less (distance: 713 ± 166 vs. 769 ± 182 m, p < 0.001; time: 141 ± 33 vs. 149 ± 37 s, p = 0.008), with similar patterns for women and men. Differences between WR and NR in the use of gears 3 and 2 were more extensive for moderate compared to steeper uphill terrain. Rifle carriage increased the use of gear 2, which was negatively associated with performance. Therefore, preparing biathletes to be able to cover more distance in gear 3 WR, especially in moderate uphill terrain, may improve biathlon skiing performance.